Measuring Employer-to-Employer Reallocation - Shigeru Fujita; Giuseppe Moscarini; Fabien Postel-Vinay (Institute of Labor Economics (IZA), 2020)
We revisit measurement of Employer-to-Employer (EE) transitions, the main engine of labor market competition and employment reallocation, in the monthly Current Population Survey (CPS). We follow Fallick and Fleischman (2004) and exploit a key survey question introduced with the 1994 CPS redesign. We detect a sudden and sharp increase in the incidence of missing answers to this question starting in 2007, when the U.S. Census Bureau introduced a change in survey methodology, the Respondent Identification Policy (RIP). We show evidence of selection into answering the EE question by both observable and unobservable worker characteristics that correlate with EE mobility. We propose a selection model and a procedure to impute missing answers to the key survey question, thus EE transitions, after the introduction of the RIP. Our imputed EE aggregate series restores a close congruence with the business cycle, especially with the onset of the Great Recession, exhibits a much less dramatic drop in 2008-2009 and a full recovery by 2016, and eliminates the spurious appearance of declining EE dynamism in the US labor market after 2000. We also offer the first evidence of the (large and negative) impact of the COVID-19 crisis on EE reallocation.
Keywords: J63; E24; 330; workforce reallocation; job to job transitions; current population survey